2010
DOI: 10.1007/s10067-010-1640-y
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 promoter polymorphism −174 G/C is associated with nephritis in Portuguese Caucasian systemic lupus erythematosus patients

Abstract: Interleukin-6 (IL-6) is a multifunctional cytokine with an important pathophysiological role in systemic lupus erythematosus (SLE). The polymorphism of the IL-6 gene promoter at position -174, which appears to influence the production of this cytokine, has been associated with susceptibility to some rheumatic diseases. The aim of this study is to investigate whether the IL-6 -174 G/C polymorphism associates with lupus susceptibility or affects disease characteristics in Portuguese patients with SLE. The associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 23 publications
0
31
0
2
Order By: Relevance
“…Earlier studies showed no significant differences in allele frequencies between German SLE patients and healthy controls [22]. There were no significant differences in the allele frequencies between Portuguese [23] and Chinese [24] patients with SLE either. However, our results are in line with the results of a recent meta-analysis which proved that the −174G allele is associated with SLE mainly in the European populations and less with SLE in the Asian ones [26].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Earlier studies showed no significant differences in allele frequencies between German SLE patients and healthy controls [22]. There were no significant differences in the allele frequencies between Portuguese [23] and Chinese [24] patients with SLE either. However, our results are in line with the results of a recent meta-analysis which proved that the −174G allele is associated with SLE mainly in the European populations and less with SLE in the Asian ones [26].…”
Section: Discussionmentioning
confidence: 78%
“…The GG genotype was earlier found to be increased in Egyptian [20] and Malaysian [21] patients with SLE but no significant differences in the genotype frequencies were found between German patients and healthy controls [22]. There were no significant differences in the genotype frequencies between Portuguese [23] and Chinese [24] patients with SLE either. Probably such differences could be explained with population variations [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 promoter polymorphism (−174 G/C) is commonly investigated as a risk factor in SLE. While a study on Malaysian population found a significant correlation between homozygous G genotype and SLE susceptibility, none of the studies in Taiwan, Iran, and Portugal reported the association of this polymorphism with SLE in their populations [29, 5961]. …”
Section: Candidate Genesmentioning
confidence: 99%
“…Among these, the most studied SNP at position -174 (IL-6 -174G/C) can modify transcriptional regulation and cytokine levels, and has an impact on inflammatory phenotypes (Fishman et al, 1998). Previous studies have shown that IL-6 -174 G/C polymorphism is associated with the development and progression of various human diseases including systemic lupus erythematosus, neuroblastoma, coronary heart disease, HIV/AIDS, and nephritis (Sobti et al, 2010;Santos et al, 2011;Yin et al, 2012;Totaro et al, 2013;Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%